The relationship between reading comprehension and critical thinking among EFL learners - Alshehri, Alaa Salem (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2024)
Having students think critically is essential to their achieving a successful life, and thus, to develop the society they live in. Reading and critical thinking skills, are essential to acquiring knowledge, especially with foreign languages. This study aims to explore the relationship between reading comprehension and critical thinking among EFL learners. Forty EFL learners were given two tests: a reading comprehension test and the Arabic version of the Watson-Glaser Critical Thinking Appraisal (1980). The survey's statistical results indicate a significant and positive correlation between reading comprehension and critical thinking, particularly in inference and interpretation skills. However, three critical thinking skills (argument, assumption and deduction) seemed to be insignificant compared to the participants' reading comprehension scores. The findings, therefore, suggest some pedagogical implications. The most important implication is integrating critical thinking skills in second language skills, like reading. EFL teachers can give learners some tasks to think of reading passages related to their life, and practices can be designed based on critical thinking skills. Teachers can implement guided reading sessions that concentrate mainly on interpreting texts and drawing inferences by using tasks such as real-world scenarios and problem-solving.